FLEXURAL AND IMPACT BEHAVIOUR OF GRAPHITE REINFORCED ABS-BASED FDM COMPOSITES (International Journal of Engineering Management Science, 2018)
Particularly for engineering purposes, the development of additive manufacturing (AM) has resulted in functionally enhanced composites. Widely employed in Fused Deposition Modelling (FDM), Acrylonitrile Butadiene Styrene (ABS) is mechanically strong, cost-effective, and simple to process. But when reinforced with graphite, it will be capable of withstanding flexural and impact loads. The flexural and impact properties of graphite-reinforced ABS composites produced by the FDM process are investigated in this research. Specimen production with different composition of graphite and testing their mechanical behavior are part of the experimental method. With maximum reinforcement of graphite, the findings show spectacular improvement in the flexural strength and impact resistance.
Keywords: Additive Manufacturing, Fused Deposition Modelling, Acrylonitrile Butadiene Styrene, Impact Strength, Flexural Strength